Occupational exposure to hydrocarbons and chronic pancreatitis: a case-referent study. Issue 9 (September 1994) - McNamee, R; Braganza, J M; Hogg, J; Leck, I; Rose, P; Cherry, N M
Abstract : OBJECTIVES--To investigate the hypothesis that hydrocarbon exposure is a risk factor for chronic pancreatitis. METHODS--102 cases of chronic pancreatitis and 204 age and sex matched referents were interviewed about their occupational histories, alcohol and cigarette consumption, and diet. Exposure to hydrocarbons was inferred from interview responses by four assessors who were blind to disease state, and these data were then summarised by a cumulative hydrocarbon exposure (CHE) score. RESULTS--After adjustment for alcohol, cigarettes, dietary antioxidants, and social class, odds ratios for low CHE scores were 1.20 (90% CI: 0.62-2.35) and 2.67 (90% CI: 1.22-5.87) for high scores. A test for trend with level of exposure among only those who had exposure scores > 0 gave p = 0.09. Analysis by type of hydrocarbon was limited to four exposures for each of which there were at least 20 exposed patients. The adjusted OR for paint solvents (any level) was 0.96 (90% CI: 0.48-1.93); for diesel exhaust fumes OR = 2.66 (90% CI: 1.05-6.73); for petrochemicals OR = 1.82 (90% CI: 0.80-4.11); and for chlorinated solvents OR = 1.49 (90% CI: 0.58-3.81). CONCLUSIONS--These results support the original hypothesis. Further studies are needed to confirm or refute the findings here and to clarify the types of hydrocarbon involved.